2022
DOI: 10.1002/wnan.1808
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics, dose–response, and risk assessment of nanomaterials: Methodology, challenges, and future perspectives

Abstract: The rapid growth of nanomaterial applications has raised safety concerns for human health. A number of studies have been conducted to assess the toxicokinetics, toxicology, dose–response, and risk assessment of different nanomaterials using in vitro and in vivo animal and human models. However, current studies cannot meet the demand for efficient assessment of toxicokinetics, dose–response relationships, or the toxicological risk arising from the rapidly increasing number of newly synthesized nanomaterials. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 155 publications
0
14
0
Order By: Relevance
“…The number of NPs in the blood was assumed to be approximately equal to that in the plasma or serum. In the blood or plasma, the formation of biomolecular coronas will substantially affect the PK profile of NPs . In previous studies, the changes in targeting capabilities of NPs were reported to be impacted by the physicochemical properties, such as NP surface modification.…”
Section: The Impacts Of Individual Physicochemical Propertiesmentioning
confidence: 99%
“…The number of NPs in the blood was assumed to be approximately equal to that in the plasma or serum. In the blood or plasma, the formation of biomolecular coronas will substantially affect the PK profile of NPs . In previous studies, the changes in targeting capabilities of NPs were reported to be impacted by the physicochemical properties, such as NP surface modification.…”
Section: The Impacts Of Individual Physicochemical Propertiesmentioning
confidence: 99%
“…Recent rapid advancements in nanotechnology have enabled efficient synthesis of nanomaterials (NMs) or nanoparticles (NPs) with a variety of physicochemical properties for several different applications, such as consumer products, industrial, and medical applications. As the usage of NMs increases, human exposure to these materials inevitably intensifies. The effect of NM exposure on human health could be diagnostic, therapeutic, or detrimental depending on the NM itself (usually related to its physicochemical properties), the drug that the NM carries, the external exposure dose, frequency and duration, the internal dose at the target organ and cells, as well as the sensitivity of the species, organs, and cells. Many animal studies have shown that overexposure to NMs can cause adverse effects on different organ systems, such as the lungs, liver, and blood. A few human studies have also associated accidental or occupational exposure to NMs with adverse effects. The increasingly widespread use of NMs and the reported toxicity data have caused concern on the potential risk of NMs and raised a need to develop strategies to properly assess the risk of NMs.…”
mentioning
confidence: 99%
“…Multiple studies have attempted to develop methods for risk assessment of different NMs, including titanium dioxide, gold, and silver NPs. ,− However, existing methods/models are limited to a certain type of NMs, and some of the models have not been adequately validated due to a lack of in vitro or in vivo data. High variations in the type and physicochemical properties of NMs, the type of target cells, and the number of cells in the body, as well as the route of exposure, create an impossible task to perform risk assessment of different NMs using conventional animal toxicity data-based approaches.…”
mentioning
confidence: 99%
See 2 more Smart Citations